bioplastik PENGARUH PEMLASTIS GLISEROL DAN SORBITOL TERHADAP KARAKTERISTIK BIOPLASTIK BERBAHAN PATI UBI MBOTE - Hamzah, Imron; N, Lailatin; S, Gancang (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
Bioplastics are plastic biopolymers made from starch that are easily degraded by soil microbes and may be an alternative to traditional plastics. Mbote tuber starch may be used as the main mass for the production of bioplastics by adding glycerin and sorbitol plasticizers. This research aims to determine the influence of plasticizers with different composition. Starch making, mixing the ingredients with plasticizer, heating, printing and drying are the sequence steps of making bio-plastic. In this study, plasticizers used glycerol and sorbitol with variations in the composition of the plasticizers 0, 0.6, 0.9, 1.2, 1.5 ml. The results showed the maximum tensile strength of glycerol bioplastic (56.12 out of 0.06) MPa with elongation (5.23 to 1.43)%, for sorbitol bioplastic the maximum tensile strength was (70, 66 then 0.09) MPa and it has an elongation value (7.85 then 0.08)%. The maximum degradability test of glycerol emollient showed that the emollient volume was 46.93% and the resolution was 3.28 mg per day and it took 14 days and 9 hours to completely reduce, while the sorbitol emollient obtained meant 1, It was 2, 4%. 5 mg is required for decomposition for 11 days and 4 hours for / day and overall reduction. The maximum area test of gliserol plasticizer is volume 0,9 plastisizer was 20,00±0,39 %, for sorbitol plastisizer is volume 1,5 plastisizer wes 14,00±0,51 %. Key words : Plasticizer Glycerol and Sorbitol, Mbote tuber starch, Bio-plastics